WMNs enabled WBANs system for pilgrims’ health monitoring at overcrowded environment during hajj in Saudi Arabia: a feasibility study - al Masud, Shah Murtaza Rashid; Ahmed Ali, Ghassan (International Journal of Engineering and Technology, 2019)
Due to the hardship of expedition, instability, overcrowded environment and fluctuation of rough weather, continuous walking, hassle and mental stress during the Hajj at Makkah in Saudi Arabia, many pilgrims get injured, sick and tired. Besides, those who are suffering from various chronic diseases may also contract severe heart, chest, abdominal, and kidney diseases along with some infectious diseases like influenza and thus complicate the overall physiological functions of the patients. Other than the problems of physical sickness and diseases due to harsh and overcrowding at ritual sites also causes numerous problems which may end with the physical injury, trauma and even death along with missing or lost pilgrims. Therefore during Hajj, it is a crucial matter and a significant challenge to ensure the best healthcare services and facilities for pilgrims’ real-time health monitoring. Wireless body area networks (WBANs) is a modern and promising healthcare technology which coverage is limited to 1-2 meters. Hence, to extend the network coverage area for WBANs at Hajj ritual sites we have proposed wireless mesh networks (WMNs) to integrate with WBANs due to its self-expandable, self-configuring and self-healing nature. In this research, an extensive literature review is conducted, and a feasibility study is performed to identify the way to transmit pilgrims’ health information to the healthcare centres by integrating WBANs with WMNs.